VEGFA-dependent and -independent pathways synergise to drive Scl expression and initiate programming of the blood stem cell lineage in Xenopus. - Ciau-Uitz, A; Pinheiro, P; Kirmizitas, A; Zuo, J; Patient, R (2013)
The first haematopoietic stem cells share a common origin with the dorsal aorta and derive from putative adult haemangioblasts in the dorsal lateral plate (DLP) mesoderm. Here we show that the transcription factor (TF) stem cell leukaemia (Scl/Tal1) is crucial for development of these adult haemangioblasts in Xenopus and establish the regulatory cascade controlling its expression. We show that VEGFA produced in the somites is required to initiate adult haemangioblast programming in the adjacent DLP by establishing endogenous VEGFA signalling. This response depends on expression of the VEGF receptor Flk1, driven by Fli1 and Gata2. Scl activation requires synergy between this VEGFA-controlled pathway and a VEGFA-independent pathway controlled by Fli1, Gata2 and Etv2/Etsrp/ER71, which also drives expression of the Scl partner Lmo2. Thus, the two ETS factors Fli1 and Etv6, which drives the VEGFA expression in both somites and the DLP, sit at the top of the adult haemangioblast gene regulatory network (GRN). Furthermore, Gata2 is initially activated by Fli1 but later maintained by another ETS factor, Etv2. We also establish that Flk1 and Etv2 act independently in the two pathways to Scl activation. Thus, detailed temporal, epistatic measurements of key TFs and VEGFA plus its receptor have enabled us to build a Xenopus adult haemangioblast GRN.